A imputabilidade penal do serial killer portador do transtorno de personalidade psicopática - Passos, Bruna Barroso (2019)
It seeks to investigate the criminal liability of agents who commit serial homicide in Brazil. Such subjects, known as serial killers, have specific characteristics, that is, the time interval between crimes; the number of victims; the type of victim selected; the place where the crime will be committed; the modus operandi; and the signature of the criminal. In doing so, he notes that there are two types of serial killers: disorganized people who have disabling mental illness, which is due to the application of the security measure, and organized serial killers who have psychopathic personality disorder. It uses the interdisciplinarity with Forensic Psychiatry and Legal Psychology to find the adequate modality of responsibility in the theoretical and practical plans for serial psychopathic killers, defending thus, the criminal imputability. Psychopathy as a personality disorder does not meet the requirements of Article 26 of the Criminal Code. In addition, it suggests two forms of prevention of criminal recidivism of these agents, since the mere application of prison sentences does not prove effective, being they the application of the program developed by the psychologist Robert Hare in the prison environment, and the creation of a National Registry of serial killers to be used by police and members of national security